Analisa Pengaruh Variasi Bevel Dan Penggunaan Backing Ceramic Terhadap Kekuatan dan Defect Material Baja Grade A Pengelasan Shield Metal Arc Welding (SMAW) - Muflih, Abdullah; Sangadji, Ramli; Hamid, Abdul; Sutrisno, Sutrisno; Wa’addulloh, Mu’izzaddin (Jurnal Universal Technic, 2025)
Grade A steel plates are commonly used in marine and offshore structures due to their high corrosion resistance. This study investigates the effect of bevel angle variations (30°, 40°, and 50°) and the use of ceramic backing on the mechanical properties and welding defects of Grade A steel using the Shielded Metal Arc Welding (SMAW) method. Welding was conducted with four-pass multipass welding. An experimental approach was employed, including macro visual inspection, dye penetrant, tensile, and impact testing. Results showed that specimens without ceramic backing (P1) had more defects such as incomplete penetration and spatter compared to those with backing (P2). All specimens met ASTM E23 impact standards (average 23.9–24.1 J/mm²). Tensile tests revealed that ceramic backing improved strength, with the highest UTS (576.1 MPa) and elongation (25%) found.